ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN KERIPIK PISANG SUSU LAMPUNG - Cindy Cilvia Christianti; Tri Endar Suswatiningsih; Resna Trimerani (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The over production of banana in Lampung province makes processing business of milk banana chips in this area growing rapidly,either in Metro City. Because of that, in order to win the competitive market competition, the businessmen of milk banana chips must have marketing strategy as weapons to compete. One of the applied marketing strategy is marketing mix. The purpose of this study is to describe the marketing mix (product, price, place, and promotion) implemented by Home Industry Keripik Pisang Tunas Metro. The method used in this study is descriptive quantitative and the determination of the study location is by case study. The sampel definition is using Key Person method, which is the owner, secretary, exchequer, and the employee of the marketing department of the Home Industry Keripik Pisang Tunas Metro. This study uses secondary data for 2014-2021. The result of the study show that the marketing mix strategy which consist of product, price, place, and promotion simultaneously or partially affect the Keripik Pisang Tunas sales volume significantly, where the product variable has the most dominant influence compered to price, place, and promotion variable.